Ideologies Et Terminologies Associees A L’homosexualite Chez Les Populations De Bouake, Cote d’Ivoire - Parfait, Kouakou Tehua (European Scientific Journal, ESJ, 2017)
The populations of Bouaké in general have extremely negative perceptions of homosexuality. They translate this aversion by a whole lexical field with depreciative and offensive connotations in refering to it. On the other hand, there are homosexuals who have positive perceptions, and who, in order to escape social reprobation, secretly live their sexuality while at the same time developing a jargon that allows them to first recognize each other and then value themselves. This homophobia is not without dramatic consequences for homosexuals as well as for society itself. There is therefore a need to work at all levels (family, legal, political etc.) to curb homophobic acts before the worst happens.